Development and validation of a new knowledge, attitude and practice questionnaire on allergic rhinitis patients towards intranasal corticosteroid usage - Retinasekharan, Senthilraj (2018)
Intranasal corticosteroids (INCS) are presently the most effective overall treatment for allergic rhinitis (AR) and are first-line therapy for adults in moderate-to-severe cases of allergic rhinitis or in individuals who are still symptomatic despite the regular use of antihistamines. Although INCS are the most commonly prescribed AR treatment, less than half of patients are fully satisfied with their INCS. Most patients discontinue treatment due to lack of long-lasting symptom relief and other various reasons side. In spite of numerous studies and the appreciation of the clinical importance of INCS usage for AR patients, research in this area has been impeded by absence of a questionnaire devoted to an assessment of self-reported evaluation of knowledge, attitude and practice of AR patients towards INCS usage. This study was designed to assess the knowledge, attitude and practice (KAP) of allergic rhinitis patients towards intranasal corticosteroids usage. Methods: This cross-sectional questionnaire study was conducted in two tertiary hospitals. The process comprised of development and validation stages. The development phase encompassed a literature review, expert panel review, focus group testing, and evaluation of the developed questionnaire. The validation phase consisted of content validity, face validity, construct validity, exploratory factor analysis and test-retest method. Cronbach’s alpha was used to verify internal consistency. A revised final version was drafted. The knowledge segment consists of five questions, attitude segment consists of five questions and the practice segment consists of four questions. Results: There were 77 participants were enrolled. Twenty of them (26%) have mild intermittent, 32 (41.6%) have mild persistent and 25 (32.5%) have moderate severe persistent AR. Ninety five percent indicated they understood the questions and found them easy to answer. Ninety percent indicated the appearance and layout were acceptable. Explanatory factor analysis revealed four factors associated with KAP. The Cronbach’s alpha of the four factors ranged from 0.614 and 0.809. The final questionnaire composed of the knowledge segment consists of four questions, attitude segment consists of four questions and the practice segment consists of four questions was valid and reliable. Conclusions: The instrument has satisfactory reliability and validity indices and can be used to measure AR patients’ knowledge, attitude and practice regarding INCS usage. This study acts as a stepping stone towards deriving the KAP among AR patients to better understand and in turn improve treatment outcome by educating patients and rectifying their perception towards INCS usage.